Green Synthesis of Titanium Oxide Nanoparticles Using Potato Peel Extract and Investigation of Their Structural and Morphological Properties: Sintesis Ramah Lingkungan Partikel Nano Oksida Titanium Menggunakan Ekstrak Kulit Kentang serta Kajian Sifat Struktur dan Morfologinya - Ahmed Naser Hussein AlHusseini (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Nanotechnology offers advanced approaches for developing functional materials with unique physicochemical properties. Specific Background: Titanium dioxide nanoparticles are widely studied due to their stability, non-toxicity, and applicability in photocatalysis and environmental remediation. Knowledge Gap: Conventional synthesis methods often involve toxic chemicals and energy-intensive processes, creating a need for sustainable alternatives. Aims: This study aims to synthesize TiO₂ nanoparticles using potato peel extract through a green sol-gel method and to investigate their structural and morphological properties. Results: X-ray diffraction confirmed the formation of phase-pure anatase TiO₂ with a tetragonal structure and an average crystallite size of 22.687 nm. FTIR analysis verified Ti–O–Ti bonding and surface hydroxyl groups, while FE-SEM revealed near-spherical morphology with slight agglomeration. EDX analysis demonstrated high chemical purity and homogeneous elemental distribution of titanium and oxygen. Novelty: The study utilizes potato peel waste as a biogenic reducing and stabilizing agent, contributing to sustainable nanomaterial synthesis. Implications: The obtained nanoparticles exhibit properties suitable for applications in photocatalysis, environmental remediation, and biomedical fields, supporting the development of eco-friendly nanomaterial production strategies. Keywords: Titanium Dioxide Nanoparticles, Green Synthesis, Potato Peel Extract, Structural Characterization, Nanomaterials Key Findings Highlights Phase-pure anatase structure confirmed through diffraction analysis Biogenic route produced nanoscale particles with uniform composition Surface functional groups support catalytic application potential